Disorders of Puberty in Severely Neurologically Impaired Children: Is Delayed Puberty an Underestimated Problem? - Calcaterra, Valeria; Cena, Hellas; De Silvestri, Annalisa; Di Mitri, Marco; Pelizzo, Gloria (Frontiers in Pediatrics, 2019)
Introduction In children with disabilities, precocious puberty (PP) has been reported, however there is a paucity of studies on delayed puberty (DP) in neurologically impaired (NI) children. Patients and methods We retrospectively evaluated 65 patients with severe disabilities (6-18 years). DP was considered whenever the following criteria where satisfied respectively for girls and boys, absence of breast development by age 13 or menarche by age 15, absence of at least 4 mL testicular growth volume or 2.5 cm length by age 14. PP was defined as the presence of puberty signs at <8 and <9 years of age respectively, for girls and boys. In all patients a family history of DP was obtained. A hormonal panel was evaluated when puberty disorders were detected. As a control group we evaluated 50 age-matched healthy subjects. Results Puberty disorders were observed in 12 NI patients and in one control (p<0.01). DP was detected in 8 NI subjects (3M/5F) and in one healthy boy (p=0.04), without differences between genders. Low levels of gonadotropins were detected in all NI subjects with DP. The number of subjects with a BMI<-3SDS was higher in NI patients with DP compared to NI subjects with normal puberty (p<0.01). The family history for pubertal delay was negative in all NI patients with DP and positive in the control subject. Conclusion NI children and adolescents may experience delayed pubertal changes. Pubertal development monitoring is strongly recommended to evaluate whether targeted interventions may improve outcomes.